The Effect Of The Contextual Teaching And Learning (CTL) Learning Model On The Science Learning Outcomes Of Grade IV - Sri Pebriani; Canni Loren Sianturi; Muktar B. Panjaitan (CV Putra Publisher, 2026)
This study aims to determine whether the Contextual Teaching and Learning (CTL) model has an effect on the learning outcomes of Science and Social Studies (IPAS) for Grade IV students at UPTD SD Negeri 124398 Pematangsiantar. This research is a quantitative study with an experimental approach, using a Pre-Experimental Design type “one group pretest-posttest design.” The sample of this study consisted of 22 Grade IV students at UPTD SD Negeri 124398 Pematangsiantar. Data were collected through multiple-choice tests administered before (pretest) and after (posttest) the treatment. The data analysis techniques used were the N-Gain test and hypothesis testing. The N-Gain score obtained was 0.57, which indicates that the applied learning model was quite effective in improving students’ IPAS learning outcomes. Furthermore, the hypothesis testing results showed that the calculated t-value (tcount) = 15.532 and the t-table value = 1.721, resulting in tcount > ttable (15.532 > 1.721). This demonstrates that there is a significant difference between the students’ pretest and posttest results. Thus, Ha in this study is accepted and H0 is rejected. It can be concluded that the Contextual Teaching and Learning (CTL) model has a significant effect on the IPAS learning outcomes of Grade IV students at UPTD SD Negeri 124398 Pematangsiantar